Relationships between T-scores at the hip and bone mineral density at the distal femur and proximal tibia in persons with spinal cord injury. (2nd September 2020) - Cirnigliaro, Christopher M.; Parrott, J. Scott; Myslinski, Mary Jane; Asselin, Pierre; Lombard, Alexander T.; La Fountaine, Michael F.; Kirshblum, Steven C.; Forrest, Gail F.; Dyson-Hudson, Trevor; Spungen, Ann M.; Bauman, William A.
Abstract : Objective: To identify T -score values at the total hip (TH) and femoral neck (FN) that correspond to the cutoff value of <0.60 g/cm 2 for heightened risk of fracture at the distal femur (DF) and proximal tibia (PT). Design: Retrospective analysis of data in a research center's database. Setting: Community-based individuals with spinal cord injury (SCI). Participants: 105 unique individuals with SCI. Outcome Measurements: DXA derived areal BMD (aBMD) and T -score of the DF, PT, TH, and FN. Results: The aBMD at the DF and PT regions were predictors of T -scores at the TH ( R 2 = 0.63, P < 0.001 and R 2 = 0.65, P < 0.001) and FN ( R 2 = 0.55, P < 0.001 and R 2 = 0.58, P < 0.001). Using the DF and PT aBMD of 0.60 g/cm 2 as a value below which fractures were more likely to occur, the predicted T -score was −3.1 and −3.5 at the TH and −2.6 and −2.9 at the FN, respectively. However, when the predicted and observed T -score values disagree outside the 95% limit of agreement, the predicted T -score values are lower than the measured T -score values, overestimating the measured values between −2.0 and −4.0 SD. Conclusion: The DF and PT cutoff value for aBMD of 0.60 g/cm 2 was a moderate predictor of T -score values at the TH and FN, with considerable inaccuracies outside the clinically acceptable limits of agreement. As such, the direct measurement of knee aBMD in persons with SCI should be performed, whenever possible, prior to prescribing weight bearing upright activities, such as robotic exoskeletal-assisted walking.